Biomimicking of a Swim Bladder and Its Application as a Mini‐Generator. Issue 7 (7th December 2016) - Song, Mengmeng; Cheng, Mengjiao; Xiao, Meng; Zhang, Lina; Ju, Guannan; Shi, Feng
Abstract : A model fish with a man‐made swim bladder achieves fast vertical motions based on density adjustments in a pressure‐responsive way. When exposed to a magnetic field, a mini‐generator is achieved by harvesting energy from the environment, working with pressure differences in the blood‐pressure range and at the frequency of a beating heart.